Universal Filtered Multi-Carrier System Based on Selective Mapping (Xibei Gongye Daxue Xuebao, 2019)
Internet of things (IoT) and machine-to-machine (M2M) communication are characterized by short periods and bursts. Traditional orthogonal frequency division multiplexing (OFDM) has not meet the demand for such traffic, while IoT and M2M communication will play an important role in the next fifth generation (5G) communication, so it is particularly urgent to study the small packet and low-latency wireless transmission technologies that satisfy IoT and M2M communication. Universal filter multi-carrier (UFMC) is a new kind of filtered wireless transmission mechanism that meets this requirement, but it faces a higher peak-to-average power ratio (PAPR) than OFDM, which affects the energy efficiency of UFMC. Based on the PAPR performance evaluation of several multi-carrier transmission technologies, a universal filtered multi-carrier based on selective mapping (SLM-UFMC) system is proposed, and the relationship between the number of candidate sub-bands and the performance or between the number of carriers and the performance is carried out. The simulation results show that SLM-UFMC can effectively reduce the PAPR of UFMC system, and the PAPR performance is improved by 1.8 dB comparing with the traditional UFMC. It also further indicates that SLM-UFMC is more suitable for IoT and M2M communication in 5G communication.